A long time to get home : rejection of closure and the role of the reader in hybrid texts : Lost and Gone Away by Lynn Jenner & Nox by Anne Carson : a critical-creative thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy (Creative Writing) at Massey University, Albany, Aotearoa New Zealand. EMBARGOED until further notice. - Wilson, Annabel (Massey University, 2023)
A long time to get home is a critical-creative thesis that asks the research question: In what ways can the strategies and techniques of hybrid works articulate responses to loss? My thesis approaches this question from a writer’s perspective. Part One examines how two hybrid books about searches of different kinds, Lost and Gone Away (2015) by Lynn Jenner and Nox (2010) by Anne Carson, enact tensions between language and loss. This essay focuses on the genre-blurring strategies and techniques that make these case studies what Lyn Hejinian calls "open texts" (Language 43), which favour the “border” (“Two Talks”, “Continuing”). Drawing on Hejinian’s concept of “the rejection of closure” (Language 40), I look at how Lost and Gone Away and Nox invite the reader into an ongoing production of meaning. I show how they each reject closure, making the search for words to speak loss a continuous, communal activity. The critical investigation is the basis for my creative writing in Part Two. In conversation with the case studies and concepts addressed, the manuscript engages with my personal experience of, and process of writing around, loss. The manuscript comprises two separate pieces that are stylistically and thematically connected. Entitled Waiariki, the first is a collage of memories of a place and a person of significance to me. Its counter-piece, Where Were You?, is a fictionalised day in the life of an art gallery guide, set on March 15 2019. Within each work, I explore intersections of visual elements, prose, and poetry to build a hybrid text that circles themes of personal and public trauma and their repercussions and echoes. The weighting for this thesis is 40% critical and 60% creative. Due to the hybrid and fragmented nature of the creative component, its page count has greater relevance than the comparative word count.
Keywords: Jenner, Lynn; Lost and gone away; Carson, Anne; Nox; Literature, Experimental; New Zealand; Themes, motives; Loss; 360201 Creative writing (incl. scriptwriting)